Indonesia's Legal Policy During COVID-19 Pandemic: Between the Right to Education and Public Health - Ramadani, Rizki; Hamzah, Yuli Adha; Mangerengi, Arianty Anggraeni (JILS (Journal of Indonesian Legal Studies), 2021)
Basically, every country is obliged to ensure quality education without discrimination against every citizen, including Indonesia. Recognition of the right to education is so important that it becomes one of the goals of the state as stated in the Preamble of the 1945 Constitution, namely to educate the nation's life. However, since the COVID-19 pandemic hit the world, the education sector has also been affected. People have no choice, but to implement the Covid-19 prevention habits and protocols. In the case of Indonesia, the government has closed the schools and universities since mid-March 2020 and switched to the online learning system. In this article, the author will explain the Indonesia’s legal policy in fulfilling the community’s right to education during pandemic, at the same time analyzing how government responds to the public demands. This normative legal research is conducted using a conceptual and statutory approach, which will then be analyzed descriptive-qualitatively. The result shows that educational policies during COVID-19 pandemic can be divided into two phases: early pandemic and new normal transition. In the first phase, the government focused on protecting the health and safety to all communities in the education institution areas by implementing certain protocols, closing the schools and switching to distance/online learning. Although public health and safety are top priorities, the policies resulted in disparities among students. While in the new normal transition phase, The government tends to respond to public demands on education problems by loosening its policies a little through schools disclosure and providing the internet support in online learning